Demand and Influencing factors for community health services during chemotherapy of patients with advanced cancer - Qianqian Li; Xunrui Chen; Wenying Zhang; Haihua Yuan; Yanjie Zhang; Bin Jiang; Feng Liu (Chinese General Practice Journal)
Background: Implementing effective, rational support and comprehensive services for patients with advanced cancer undergoing chemotherapy is a significant challenge in community health services. According to recent data, the mortality rate from malignant tumors in Shanghai residents now ranks second only to cardiovascular and cerebrovascular diseases. Attention toward patients with advanced cancer undergoing chemotherapy is gradually increasing. This study aims to understand the primary care demands of such patients and the factors influencing these demands. Objective: To investigate the demand and influencing factors for community health services during chemotherapy for patients with advanced cancer in Shanghai and to develop community interventions and services tailored to these patients' demands. Methods: Patients with advanced cancer undergoing chemotherapy who regularly visited or were hospitalized at Shanghai Ninth People's Hospital, Wusong Hospital and Shanghai Baoshan Hospital of Integrated Traditional Chinese and Western Medicine from December 2021 to March 2022 were selected as the study subjects. Based on government specifications, previous research findings from surveys on questionnaires and interviews, the final version of the ''Community Health Services Demand Questionnaire for Patients with Advanced Cancer in Shanghai'' was developed. It includes three demand dimensions (psychological, medical care, social support) and 38 demand items. The contents cover general information such as demographic and sociological information(educational level, marital status, source of medical expenses, disposable monthly household income, patient group participation), and tumor diagnosis(type and time of diagnosis, pain score, comorbidities), along with items on psychological demand (6 items), medical care demand (24 items), and social support demand (8 items). A 3-point scale was employed: 1 for unnecessary, 2 for necessary, and 3 for very necessary. Demand levels were ranked according to the average score of each item. Logistic regression analyses were used to identify the influencing factors of community health service demand among these patients. Results: The demand dimensions, ranked from highest to lowest, were psychological demand (2.31 points), medical care demand (2.27 points), and social support demand (2.18 points). The top five demands were “preparation for pathological tests such as routine blood, liver and kidney functions before chemotherapy” (2.48 points), “education on chemotherapy knowledge” (2.48 points), “care for peripherally inserted central catheter(PICC) catheterization during chemotherapy” (2.45 points), “management of myelosuppression after chemotherapy” (2.43 points) and ''providing updated information on treatment, examination and rehabilitation” (2.42 points), primarily focusing on the medical care demand dimension. Logistic regression analysis showed that educational level and disposable monthly household income significantly influenced psychological demand, while age and source of medical expenses influenced medical care demand, and age and patient group participation affected social support demand (P < 0.05). Conclusion: Patients with advanced cancer undergoing chemotherapy have specific demands for community health services across psychological, medical care, and social support dimensions, influenced by factors such as age, educational level, and household income. This study offers recommendations for community health centers to develop relevant medical services. Future initiatives could introduce new service items in high demand and monitor the effectiveness of community interventions, such as psychological and medical care support for these patients, to improve their quality of life.